Funkcjonowanie leśnych przedszkoli – Waldkindergaerten – w Niemczech a obraz dzieciństwa we współczesnym świecie - Pieprzyk, Maria (Kultura-Społeczeństwo-Edukacja, 2015)
The paper deals with the issue of forest kindergartens as presented in the German concept of Waldkindergarten. This concept makes a new way of thinking about child pedagogy. These kindergartens are designed to support the child in its creative process along the fact to encourage the child to further explore the surrounding nature. These specific institutions might be regarded as an answer to the challenges of modern childhood, in which the child is exposed to a toxic environment. This very toxicity could be regarded also metaphorically as a pollution of the mind through media and technology.